ISLAMIC COOPERATIVES: OPERATIONS AND EVIDENCE FROM ORGANIZATION OF ISLAMIC COOPERATION (OIC) COUNTRIES (International Journal of Islamic Business, 2023)
The Islamic finance industry has only been dominated with Islamic banking, Takaful, Islamic capital, and the money market, although, the Islamic cooperative (I-Coop), which is a non-financial institution in most cases is yet to be fully adopted in the contemporary Muslim societies. The Islamic cooperative can be a development reform tool or a social and economic growth method, it can be used to offer interest-free loans and to cover specific demands in rural and urban settings. The main purpose of this study is to investigate Islamic cooperative operations in some OIC countries. This study adopted the content analysis method by reviewing literature as the evidence to demonstrate and provide insights into various critical factors that have prompted the establishment of Islamic cooperatives in some OIC countries. Samples of literature for OIC countries were found and examined. Three I-Coop membercountries were given focus to (Malaysia, Indonesia, and Nigeria). The findings show that Islamic cooperatives only exist in few OIC countries. It was found that the OIC countries have emphasised more on operating Islamic banking rather than Islamic cooperatives. It was also noticed that the lack of the well-regulated Islamic cooperatives in these countries is due to lack of the government support to established it. However, in Nigeria, the Islamic cooperative is considered new, but the study found various types of Islamic cooperatives already operating there. Lastly, based on the experiences of the Islamic cooperatives in the selected countries, the study suggested creating more awareness, promotions, and guidelines most especially within the OIC countries.